Severity illness scoring systems for early identification and prediction of in-hospital mortality in patients with suspected sepsis presenting to the emergency department - Geier, Felicitas; Popp, Steffen; Greve, Yvonne; Achterberg, Andreas; Gloeckner, Erika; Ziegler, Renate; Mang, Harald; Christ, Michael; Heppner, Hans Jürgen (Wiener Klinische Wochenschrift, 2013)
The in-hospital mortality of patients with severe sepsis and septic shock (SSSS) is high. In this study we examined the diagnostic and prognostic accuracy of the emergency severity index (ESI), the modified early warning score (MEWS), and the mortality in emergency department (ED) sepsis (MEDS) score. This is a single-centre, prospective and observational study of 151 consecutive patients presenting to the ED of the Nuremberg Hospital with suspected sepsis (age 68.3 ± 18 years, 54.3 % men, 45 % with SSSS, in-hospital mortality of SSSS: 27.8 %). In this study, 37.7 % of the studied patients had a urinary tract infection (n = 57/151), 33.8 % a pneumonia (n = 51/151), 8.6 % an acute abdominal infection (n = 13/151), and in 12.6 % the focus of infection was not further specified or identifiable (n = 19/151). The diagnostic and prognostic accuracy was analyzed by means of the receiver operating characteristic (ROC) curve. The areas under curve (AUC) in terms of diagnostic accuracy were 0.609, 0.641, and 0.778 for the ESI, MEWS, and MEDS score respectively. The AUCs concerning prognostic accuracy were 0.617, 0.642, and 0.871 for ESI, MEWS, and MEDS score respectively. By using the MEDS score systematically, critically ill patients with sepsis could be detected in the ED. Finally, the MEDS score provides the basis for a risk adjusted disposition management that follows objective criteria. © 2013 Springer-Verlag Wien.
CRIS-Team Scopus Importer:2022-09-26
Keywords: early identification; emergency department; prognosis; sepsis; severityillness scoring systems